Progressive collapse analysis of precast reinforced concrete beam-column assemblies with different dry connections - Zhao, Zidong; Cheng, Xiaowei; Li, Yi; Diao, Mengzhu; Guan, Hong; An, Yi (Engineering structures, 2023)
•Conduct tests on PC beam-column assemblies with dry connections.•Establish high-fidelity 3D numerical models of PC beam-column assemblies.•Investigate influence of connection defects on collapse resistance performance.•Optimize existing connection types for PC beam-column assemblies.•Identify resistance contributions from different resisting mechanisms. Beam-column joints using dry connections usually experience severe damage under large deformations, causing precast concrete (PC) frames with dry connections to become highly vulnerable to progressive collapse. Hence, this study conducted a static pushdown test adopting uniformly distributed loading on four PC beam-column assemblies using dry connections and one reinforced concrete (RC) substructure to investigate the collapse-resisting behavior under the middle-column removal scenario. The tested dry connections included top-and-seat angle connection (TA), strengthened top-seat angle connection (STA), and two refined connections with unbonded post-tensioning tendons (UPTA and UPSTA, respectively). Results showed that compared with specimen RC, the resistance of specimen TA at the beam flexural and compressive arch action (B-CAA) and catenary action (CA) stages dropped by 41% and 27%, respectively, due to the buckling of steel angles and endplates (B-CAA) and the fracture of steel angles and bolts (CA). Specimen STA had a 7% greater resistance of B-CAA because of the strengthened steel angles. However, the ductility decreased, with the displacement of rebar fracture decreasing by 37%, leading to a 30% resistance reduction of CA. The unbonded post-tensioning tendons dramatically improved the structural integrity, contributing to 52% and 97% increase in the resistance of the CA of UPTA and UPSTA, respectively. Further numerical analyses indicated that the restraint gaps reduced the initial stiffness of the collapse responses, and a good rebars welding anchorage condition could remarkably improve the resistance in the B-CAA and CA stages. An improved joint was proposed based on UPTA and rebar welding anchorage to improve deformation capacity while retaining reasonable collapse resistance. Finally, the resistance contributions from different mechanisms and components were identified through a developed calculation procedure.